2010
DOI: 10.1016/j.ijpara.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni host-exposed surface antigens characterized by sera and recombinant antibodies from schistosomiasis-resistant rats

Abstract: Antibodies from Schistosoma mansoni-infected rats, unlike mice, show a higher titer for schistosome apical tegumental antigens compared with non-apical membrane antigens. These antibodies bind to the surface of living lung stage worms and to formaldehyde-fixed adult worms. We produced a singlechain antibody Fv domain (scFv) phage library displaying the antibody repertoire of rats highly immune to schistosome infection and we selected for scFvs that recognize the host-exposed surface of worms. Five unique rat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
1
25
0
3
Order By: Relevance
“…Antischistosomal antibodies were also reported to bind to the surface of PZQ-treated worms [23]. It has been amply documented that host antibodies fail to bind to the surface membrane of intact healthy schistosomes in vivo [24] or in vitro [18,25]. In the study by Sepulveda et al [25], antibodies were able to bind to the surface of adult worms incubated in formaldehyde, which is able to permeate the outer lipid bilayer and cross-link proteins, leading to tegumental disorganisation that allows antibody access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antischistosomal antibodies were also reported to bind to the surface of PZQ-treated worms [23]. It has been amply documented that host antibodies fail to bind to the surface membrane of intact healthy schistosomes in vivo [24] or in vitro [18,25]. In the study by Sepulveda et al [25], antibodies were able to bind to the surface of adult worms incubated in formaldehyde, which is able to permeate the outer lipid bilayer and cross-link proteins, leading to tegumental disorganisation that allows antibody access.…”
Section: Discussionmentioning
confidence: 99%
“…It has been amply documented that host antibodies fail to bind to the surface membrane of intact healthy schistosomes in vivo [24] or in vitro [18,25]. In the study by Sepulveda et al [25], antibodies were able to bind to the surface of adult worms incubated in formaldehyde, which is able to permeate the outer lipid bilayer and cross-link proteins, leading to tegumental disorganisation that allows antibody access. Extraction of adult worm surface membrane cholesterol with methyl-␤-cyclodextrin, and ARA-mediated NSMase activation and subsequent hydrolysis of surface membrane SM, reproducibly led to surface membrane exposure and specific antibody access [18].…”
Section: Discussionmentioning
confidence: 99%
“…This means the worms were mostly exposed to the treatment in the same location. Although it is not known which antigens, it is suggested that tegumental antigens of schistosomes vary as the worms mature from cercaria to schistosomule to adult which is thought to be a protective mechanism (Sepulveda et al 2010). This therefore suggests there are worm structural differences that may have led to the two extracts having more pronounced activity in either the 3 week or 4 week old worms.…”
Section: Discussion:-mentioning
confidence: 99%
“…Knowledge of these antigens is not just important for the immunobiology of schistosomiasis but specifically could be exploited for the discovery and development of vaccines and diagnostics. The rat has long been used as a model of immunological resistance for both S. japonicum 7 , 8 , 18 , 59 and S. mansoni 10 , 11 , 15 , 60 infection. Consequently, we screened serum and tissue antibodies from the rat using a protein microarray.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, immunity and infection severity vary considerably among these hosts allowing for comparison between susceptible and resistance traits. Of the laboratory animals, the mouse is fully permissive, passing viable schistosome eggs, whereas the rat ( Rattus norvegicus ) is semi‐permissive to both S. japonicum 7 , 8 and S. mansoni 9 , 10 , 11 infections. The resistant characteristics of the laboratory rat have been used for several decades in vaccine research 2 , 10 and resulted in the identification of the only schistosome vaccine antigen, Sh28GST, currently in phase III trials 4 , 12 , 13 .…”
mentioning
confidence: 99%